유통업 근로자의 직장폭력 경험 실태 - 김숙영(Souk Young Kim); 윤순녕(Soon Nyung Yun) (지역사회간호학회지, 2012)
Purpose: The purpose of this study is to explore violence experienced by workers in the distribution industry. Methods: The research subjects were 236 workers from 2 department stores and 1 large scale discount store located in Daejeon City, Korea. The collected data were analyzed through descriptive statistics, $x^2$-test, and logistic regression analysis. Results: 72.9% of the research subjects experienced verbal violence, and 9.3% of the respondents experienced physical violence during last year. 17.8% of the respondents reported that they had experience of sexual harassment at their workplaces. The variables which affected verbal violence included working departments and stress level, whereas the variable that affected physical violence was educational level of workers. The variables that affected experience of sexual harassment turned out to be gender as well as the duration of work at the current workplaces. Conclusion: The findings from this research revealed that many of the workers engaged in the distribution industry were exposed to workplace violence. For the reduction of risk of workplace violence for these workers, it is required to develop and execute programs including violence related policies and education about workplace violence.